Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1037/apl0000358
|View full text |Cite
|
Sign up to set email alerts
|

Say it as it is: Consequences of voice directness, voice politeness, and voicer credibility on voice endorsement.

Abstract: To gain endorsement from their managers, should employees be direct with explicit change suggestions, or should they be indirect with questions and hints? We draw on psychological threat and communication clarity theories to offer competing hypotheses with respect to the association between voice directness and managerial endorsement. We then further draw from social judgment research to theorize whether the relationship between voice directness and managerial endorsement might be modified by voicer politeness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
141
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(161 citation statements)
references
References 95 publications
(137 reference statements)
4
141
0
3
Order By: Relevance
“…Whereas recent work has started to move beyond main effects towards interactive effects of message, sender, context, and receiver attributes on voice endorsement (e.g. Lam et al, 2018;Sijbom et al, 2015b;Urbach & Fay, 2018), we propose that our construal-level approach can further advance this emerging area of investigation by offering a unifying principle to guide studies examining different components of voice communication (see Lee, 2019). Although this construal-level approach is not all-encompassing (see below), it nevertheless can encompass many instantiations of message factors (e.g.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas recent work has started to move beyond main effects towards interactive effects of message, sender, context, and receiver attributes on voice endorsement (e.g. Lam et al, 2018;Sijbom et al, 2015b;Urbach & Fay, 2018), we propose that our construal-level approach can further advance this emerging area of investigation by offering a unifying principle to guide studies examining different components of voice communication (see Lee, 2019). Although this construal-level approach is not all-encompassing (see below), it nevertheless can encompass many instantiations of message factors (e.g.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…The theory's two central conceptsmessage framing and psychological distancecan be operationalized in myriad ways (Davidson & Van Dyne, 2017). For example, the theory's distinction between high and low construal levels may give rise to new voice typologies, such as polite versus colloquial voice, indirect versus direct voice (see Lam et al, 2018), desirability-focused versus feasibility-focused voice, and idealistic versus pragmatic voice. Similarly, accounting for psychological distance in voice endorsement should be increasingly relevant in today's workplace where managers are leading diverse employees (conducive to variability in social distance) in a global workplace (conducive to variability in spatial distance).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study (Lam, Lee, & Sui, 2018), researchers have observed that supervisors are more likely to endorse employees' suggestions when employees are more credible and polite.…”
Section: Outcomes Of Voice Behaviormentioning
confidence: 99%
“…Only a few studies examined the outcomes of employee voice behavior (e.g., Howell et al, 2015). Among the studies examining the outcomes of voice behavior, even fewer studies examined supervisor voice endorsement and voice implementation (Burris, 2012;Howell et al, 2015;Lam et al, 2018).…”
Section: Theoretical Implicationsmentioning
confidence: 99%